PENGARUH PENAMBAHAN ABU CANGKANG KELAPA SAWIT SEBAGAI SUBSTITUSI PADA SEMEN PCC TERHADAP KUAT TEKAN BETON - Stevens, Leo; Firdaus, Firdaus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to determine the results of the effect of adding palm kernel shell ash as a substitute for Pcc cement on the compressive strength of concrete. This research was conducted at the Civil Engineering Laboratory, Campus C, Bina Darma University. The object used in this research is the effect of adding palm kernel shell ash as a substitute for Pcc cement on the compressive strength of concrete with percentages of 5%, 10% and 15%. The aim is to determine the compressive strength value of concrete substituted for PCC cement in the concrete mixture and to find out optimum percentage of palm shell ash as a substitute for PCC cement. The use of Palm Shell Ash in the concrete mixture will have an influence on the slump of the concrete. The higher the level of Palm Shell Ash used, the lower the slump value. The compressive strength value of Normal Concrete is the highest strength value of Palm Shell Ash concrete with a percentage of 5%, 10%, 15% at 28 days with a value of 13.63 Mpa, while the Compressive Strength Value of Palm Oil Shell Ash Percentage is 5% with a value of 12.52Mpa , a percentage of 10% with a value of 12.44 Mpa and a percentage of 15% with a value of 11.34 Mpa. Keywords: Concrete, Press, Palm Shell